QARAQALPAQ TILIN AVTOMATIK TÚRDE ANALIZLEWDE MASHINALÍQ OQÍTÍW ALGORITMLERIN QOLLANÍLÍW - Abdalieva, G.R.; Uteuliev, N.U.; Kalmuratov, B.K. (ILIM hám JÁMIYET, 2025)
This article explores the application of machine learning algorithms for the automatic analysis of the Karakalpak language. It describes the processes of automated analysis, including morphology, syntax, and semantics, and examines the technical capabilities of the algorithms. The creation and analysis of language corpora using Python programming and its libraries are highlighted.